Humanitarian Facts In Nawal Sa'dawi’s Mautu Ma'aliyyi Al-Waziru Sabiqan: Genetic Structuralism Of Lucien Goldmann - Sihabudin Alawi; Muhammad Abdul Halim; Khomisah Khomisah (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
The novel Mautu Ma’aliyyi Al-Waziru Sabiqan emerged as a response to gender inequality and social conflict in Egypt, particularly highlighting the dominance of men over women in both the workplace and the household. This study aims to elucidate humanitarian facts, within The novel Mautu Ma’aliyyi Al-Waziru Sabiqan specifically individual and social realities, through the lens of Lucien Goldmann's genetic structuralism. Employing a descriptive qualitative methodology, this research utilizes Goldmann's genetic structuralism approach. The primary data source consists of the text of Mautu Ma’aliyyi Al-Waziru Sabiqan by Nawal Sa'dawi, which was gathered through reading, note-taking, and classification techniques, and analyzed using interpretive methods based on the descriptive framework of genetic structuralism. The study uncovers two key findings. First, at the individual level, the Prime Minister is portrayed as grappling with inner turmoil manifested through anger, sadness, and regret. Second, on a societal level, the novel reflects the realities of Egypt, particularly the prevailing male dominance over women, which corresponds with the social data from the period in which this work was produced. The narrative of the novel illustrates the alignment between fictional representation and social facts, while also exposing the complexities of Egyptian social constructs, especially concerning gender roles in professional and domestic spheres. This research contributes to the field by applying Lucien Goldmann's genetic structuralism framework to analyze the interplay between Arabic literary works and the Egyptian social context. These findings enhance Arabic literary studies by illustrating how social dynamics are both shaped by and represented in literary expressions, thereby expanding the understanding of the relationship between texts, social structures, and societal ideologies. Abstrak Novel Mautu Ma’aliyyi Al-Waziru Sabiqan muncul atas respon ketimpangan gender dan konflik sosial di Mesir, terutama dominasi laki-laki atas perempuan di tempat kerja dan rumah tangga. Penelitian ini bertujuan untuk mendeskripsikan fakta-fakta kemanusiaan, dalam Novel Mautu Ma’aliyyi Al-Waziru Sabiqan terkhusus fakta individu dan fakta sosial berdasarkan kajian strukturalisme genetik Lucien Goldmann. Penelitian ini menggunakan metode kualitatif deskriptif dengan pendekatan strukturalisme genetik Lucien Goldmann. Sumber data utama adalah teks novel Mautu Ma’aliyyi Al-Waziru Sabiqan karya Nawal Sa’dawi yang dikumpulkan melalui teknik baca, catat, dan klasifikasi dan dianalisis melalui teknik interpretasi berdasarkan metode deskriptif strukturalisme genetik. Penelitian ini mengungkap dua temuan utama. Pertama, pada level individual, tokoh Perdana Menteri digambarkan mengalami pergulatan batin berupa kemarahan, kesedihan, dan penyesalan. Kedua, pada level sosial, novel merefleksikan realitas Mesir, khususnya dominasi laki-laki atas perempuan, yang selaras dengan data sosial pada masa karya ini lahir. Narasi novel menunjukkan kesesuaian antara realitas fiksi dan fakta sosial, sekaligus menyingkap kompleksitas konstruksi sosial masyarakat Mesir, terutama terkait peran gender dalam pekerjaan dan rumah tangga. Kontribusi penelitian ini terletak pada penerapan kerangka strukturalisme genetik Lucien Goldmann untuk menganalisis relasi antara struktur karya sastra Arab dan konteks sosial Mesir. Temuan ini memperkaya kajian sastra Arab dengan menunjukkan bagaimana dinamika sosial membentuk dan direpresentasikan melalui karya sastra, sekaligus memperluas pemahaman tentang hubungan antara teks, struktur sosial, dan ideologi masyarakat.